Nature of financial distress and its prediction: an empirical study towards testing the existing models and developing a new model in Turkey - Muzır, Erol (My University, 2004)
Name - Surname : Erol Muzır Field : Management Programme : Accounting and Finance (English) Supervisor : Associate Prof. Figen Öker Degree Awarded and Date : Master - July 2004 Capital structure decisions, financial risk, financial distress and bankruptcy, prediction of financial distress.

NATURE OF FINANCIAL DISTRESS & ITS PREDICTION: AN EMPIRICAL STUDY TOWARDS TESTING THE EXISTING MODELS AND DEVELOPING A NEW MODEL IN TURKEY Severe economic conditions and the latest economic crises experienced in the Turkish economy during the last decade have had disturbing and harmful impacts on the real and financial sectors. Because of these impacts, firms and corporations have faced so a serious dilemma, which is called financial distress. Even, this problem has caused many of them to go bankrupt and involuntarily exit the economy. In fact, it has been a common concern of not only the developing but also the developed countries for many years. As financial distress refers to an unfavorable microeconomic situation for business entities, this phenomenon and its prediction have become a significant field for academicians and practitioners to study in. As a result of this great interest, many researches have been carried out to develop appropriate and well-functioning models for predicting financial distress and bankruptcy. As part of this recent trend, this study has been aimed at testing the existing financial distress prediction models in Turkey along with an additional attempt to derive a new model unique to our country. The final goal is to provide a functional mechanism to the parties with any stake in corporations for predicting corporate failure. Soyadı : Erol Muzır letme Program : Muhasebe ve Finansman (İngilizce) gen Öker Tez Türü ve Tarihi : Yüksek Lisans - Temmuz 2004 Sermaye yapısı kararları, finansal risk, finansal başarısızlık ve iflas, finansal başarısızlık tahmini. ÖZET FİNANSAL BAŞARISIZLIK VE TAHMİNİ : MEVCUT TAHMİN MODELLERİNİN TÜRKİYE'DE TEST EDİLMESİ VE YENİ BİR MODEL GELİŞTİRMEYE YÖNELİK AMPRİK BİR ÇALIŞMA Son on yıl içerisinde Türkiye ekonomisinde yaşanılan ağır ekonomik koşulların ve büyük ekonomik krizlerin reel sektör ve finans sektörü üzerinde yıkıcı etkileri olmuştur. Bu yıkıcı etkiler nedeniyle firmalar finansal başarısızlık gibi çok ciddi bir problemle karşı karşıya kalmışlardır. Hatta bu sorun birçok firmanın iflas etmesine ve ekonomiden silinmesine sebebiyet vermiştir. Aslında bu kavram, sadece Türkiye gibi gelişmekte olan ülkelerin ortak sorunu olmayıp, gelişmiş ülkeler için de önemli bir sorun haline gelmiştir. Finansal başarısızlığın işletmeler açısından arzu edilmeyen ekonomik bir olgu olması, finansal başarısızlık tahminine ilişkin çok sayıda çalışmanın gerçekleştirilmesine ve çok çeşitli tahmin modellerinin geliştirilmesine zemin hazırlamıştır. Finansal başarısızlık tahmin modellerinin keşfine yönelik mevcut bilimsel etüdlerin bir uzantısı olması suretiyle bu amprik çalışma, mevcut tahmin modellerinin Türkiye'de test edilmesi ve ülkemize özgü farklı bir modelin kurulması amacını taşımaktadır. Çalışmanın nihai amacı olarak, firmalarla çıkar ilişkisi içinde olan ilgili kesimlerin finansal başarısızlık tahmininde yararlanabilecekleri fonksiyonel bir mekanizma üretme ereği güdülmektedir.
Keywords: Banka ve bankacılık; Ekonomi; Ekonomi_Türkiye; Finansal Krizler; Finansman ekonomisi